Revolutionizing Resilience: MSMEs' Journey with Digital Strategies in Post-Pandemic Recovery - Reza Sarif; Rosya Mawaddah Susanto; Nora Ria Retnasih; Segaf Segaf (Universitas Islam Kadiri, 2023)
The Covid-19 pandemic that has occurred since 2020 has resulted in many business sectors experiencing a decline in performance, and some have even been forced to go bankrupt. This study aims to find out the digital-based strategies implemented by small, micro, and medium enterprises (MSMEs) in maintaining their business amidst economic uncertainty due to the health crisis. The method used in this study is a descriptive qualitative approach with primary data sources. The technique uses interviews with informants who are determined by purposive sampling based on certain criteria. So that in this study, 5 Respondents were business actors in the digital-based culinary field. The data analysis stage carried out in this study consisted of data reduction, then data presentation. And the next data analysis is to conclude from the information that has been obtained. The results of the study show that the digital strategy carried out by MSME actors during the economic recovery is digital marketing. By implementing this strategy, changes to the businesses run by MSME players are quite significant. This can be seen from the increase in income compared to during the pandemic. So, to be able to survive in their business, MSME players need to develop their digital literacy skills by participating in various digital marketing and digital media training.